Research on the affective domain of EFL learning : a study of motivation - Mihaljević Djigunović, Jelena (Array, 1997)
Starting from the assumption, advanced by Clement and Kruidenier, that the type of motivation for learning a second/foreign language as well as its strength is likely to be determined less by some generalized principle and more by "who learners what in what milieu", an exploratory study was carried out with Croatain learners of English. The findings show that Croatian learner posses types of motivation that differ from tose described in similar dtudies elsewhere.